Combined antifogging and antireflective double nanostructured coatings for LiDAR applications - Gärtner, Anne; Schulz, Ulrike; Sabbagh, Ahmad; Rickelt, Friedrich; Bingel, Astrid; Wolleb, Sabrina; Schröder, Sven; Tünnermann, Andreas (Optics InfoBase Conference Papers, 2022)
With commercial plasma-ion-assisted deposition technology, we generated a very convincing combination of an antireflective double-nanostructure on top of an antifog coating with long-term stable properties. The nanostructure does not affect the antifog properties and can be successfully used for LiDAR applications.
CRIS-Team Scopus Importer:2023-04-20